Clinical effectiveness of ranibizumab and conbercept for neovascular age-related macular degeneration: a meta-analysis - Wang LP; Zhang CW; Hua R (Dove Medical Press, 2018)
Luping Wang,1 Canwei Zhang,2 Rui Hua3 1Department of Ophthalmology, University of Bonn, Bonn, Germany; 2Department of Ophthalmology, Weifang Eye Hospital, Weifang, People’s Republic of China; 3Department of Ophthalmology, First Hospital of China Medical University, Shenyang, People’s Republic of China Introduction: To assess the ocular efficacy of intravitreal ranibizumab and conbercept injection in patients with neovascular age-related macular degeneration. Materials and methods: We searched PubMed, Wed of Science, Cochrane Library, EMBASE, Google Scholar, Medline, China National Knowledge Infrastructure, and WANFANG DATA databases, up to June 20, 2018. We also searched abstracts and clinical study presentations at meetings as well as trial registries; we contacted authors of included studies if questions arose. Eligibility criteria for selection of studies were randomized controlled trials and retrospective trials that compared ranibizumab with conbercept for treatment of neovascular age-related macular degeneration. Results: Eight randomized controlled trials and four retrospective studies were included with a total of 853 patients. Best-corrected visual acuity after loading dosage was improved in the conbercept group, compared with the ranibizumab group (weighted mean difference: -0.04; 95% CI: -0.07 to 0.00; P=0.04). There was a significant difference between conbercept and ranibizumab therapy with respect to unchanged or recurrent leakage of choroidal neovascularization (OR: 0.46; 95% CI: 0.24–0.88; P=0.02). No significant differences were observed in central macular thickness (weighted mean difference: -2.92; 95% CI: -9.00 to 3.17; P=0.35), complete and partial closure of leakage of choroidal neovascularization (complete closure, P=0.70; partial closure, P=0.35), or number of injections (weighted mean difference: 0.42; 95% CI: -0.46 to 1.29; P=0.35) between the conbercept and ranibizumab groups at the end of the follow-up periods. Conclusion: Pooled evidence confirmed that conbercept was superior to ranibizumab with respect to visual gain after treatment. Additional studies with long-term follow-up are needed to support our conclusion. Keywords: age-related macular degeneration, best-corrected visual acuity, central macular thickness, choroidal neovascularization, vision loss